THE DUAL ROLE OF EQUILIBRIUM PRICE IN COMPETITIVE ECONOMIES WITH ASYMMETRIC INFORMATION - Trifunović, Dejan (Economic Annals, 2008)
This paper analyses equilibrium in competitive markets with asymmetrically informed agents. In contrast to Walrasian equilibrium, where equilibrium price is only an indicator of relative scarcity, in the models studied in this paper equilibrium price has two additional roles. It conveys and aggregates the private information of agents in the economy. Each agent infers the private information of other agents by studying the equilibrium price. This implies that agents in this setting have higher cognitive capabilities than Walrasian agents. The equilibrium concept used to describe these additional roles of equilibrium price is called Rational Expectations Equilibrium (REE).